A Nationwide Survey on Patient Empowerment in Pediatric Inflammatory Bowel Disease in Germany - Kalina Kaul; Stefan Schumann; Cornelia Sander; Jan Däbritz; Jan de Laffolie (Children, 2023)
Background: The incidence/prevalence of pediatric inflammatory bowel disease (IBD) is increasing. IBD places a significant burden on young patients during important developmental stages and affects their families. Children and adolescents with IBD require increased support from health care services. However, little is known about the additional support needed and how to provide it. Therefore, a large survey was conducted with a focus on patient empowerment. Methods: For the anonymous survey, called CEDNA, a patient questionnaire for adolescents with IBD and a questionnaire for parents of children and adolescents with IBD were made available throughout Germany (distributed n = 2810). Questions covered various aspects of coping with the disease, utilization of care, use and need of information and communication services, and how information should be provided. Results: From October 2021 to April 2022, 1158 (n = 708 parents (61.1%), n = 450 patients (38.9%)) questionnaires were completed. The results show a deficit in pediatric IBD care and revealed a large gap in knowledge about core IBD topics (e.g., 74.8% of patients feel poorly informed about transition, 62.4% know little about patient organizations and self-help groups, and 54.7% have little information about preventive health measures), indicating a low level of health literacy among affected children and adolescents. Conclusion: Pediatric IBD poses significant challenges for patients, their families, and healthcare teams. By empowering patients and families, and providing targeted information and communication tailored to the age of the child or adolescent and the needs of the parents, care can be improved and better adapted to the needs of patients. Actions would include providing quality information online through scientific societies and patient organizations and facilitating self-management in adolescents.